Pore Size Distribution of Ordered Nanostructured Carbon CMK-3 by means of Experimental Techniques and Monte Carlo Simulations - Barrera Diaz, Deicy Amparo (2013)
The design and study of new materials with specific properties is interesting in several scientific and technological fields. In the last years, nanostructured carbons (NC) have rapidly attracted the attention of some researchers due to their physicochemical properties useful for many applications among them in adsorption and catalysis. In this work, the synthesis of a NC was carried out by a nanocasting method, using as a template a very ordered mesoporous material (SBA-15) and sucrose as carbon source. The final material consists of an ordered arrangement of parallel carbon nanorods bonded with some carbon nanowires (CMK-3 type), formed in the mesopores and micropores of the inorganic matrix. The inorganic matrix and the NC were structurally characterized by X-ray diffraction, texturally by N2 sorption at 77 K, and morphologically by scanning electron microscopy. The Nitrogen experimental isotherms were simulated using Grand Canonical Monte Carlo (GCMC) method based on two kernels using slit and cylindrical pore models. From these models were obtained the pore size distributions (PSD) which were compared with those obtained by Quenched Solid Density Functional Theory (QSDFT) model. The GCMC simulation showed a good agreement with experimental adsorption isotherms and some differences with the corresponding pore size distribution obtained by Density Functional Theories Methods. These correlations validate the presented GCMC method as an alternative to study in detail the porosity of these materials